UNDERSTANDING THE CREATIVE PROCESS BEHIND THE BUDHIST SONG - Kristianto, Johanes (ARTISTIC : International Journal of Creation and Innovation, 2024)
This study explores the creative process behind the Buddhist hymn Breathing In Breathing Out, specifically chosen for its recognized association with Buddhist meditation techniques. The study employs a qualitative methodology, involving five informants who possess expertise in music studies and Buddhism. Its objective is to investigate the process of creating Buddhist songs and analyze their influence on listeners. The results indicate that 1) songwriting for Buddhism is generally a voluntary pursuit without any external financial support or specified objectives, and 2) the creative process adheres to the four stages suggested by Graham Wallas. Furthermore, the practice of Breathing In Breathing Out has a beneficial impact on listeners’ mental well-being, improving mental conditions through enhanced concentration, focus, and self-acceptance.